(untitled) - Fairley, Stephen G. (Hoboken, N.J., 2008)
Increasingly, organizations are tapping into the benefits of bringing in an executive coach to help their businesses and employees achieve higher levels of success, build team proficiency, or improve employee performance; Easy to follow and apply, The Business Coaching Toolkit equips professional coaches with ten time-tested coaching techniques, providing step-by-step guidance on how and when to utilize each tool to maximize change and produce measurable results. Extensively used and perfected in a wide variety of settings, the featured tools are drawn both from the authors' own experiences as well as those of other accomplished business coaches and consultants and are designed to strengthen the coaching professional's skill set; Written for professional business coaches and consultants, professional speakers and trainers, internal coaches, and managers and executive leaders, The Business Coaching Toolkit can be used in one-on-one coaching relationships, manager-to-employee contexts, or in-group settings. This extraordinary guide enables readers to create a structured program with powerful application tools to build teams, cast vision, master priorities, and become more effective, inspired, and productive coaches.
Keywords: Executive coaching